SPECIFIC ASPECTS OF PSYCHOLOGICAL TRAINING IN MILITARY PERSONNEL - Egamov Xusan Yusupovich (Scholar Express Journal, 2022)
The spiritual harmony of the populace and the armed forces constitutes the spiritual element. The ideological-political condition of the individual's composition; the moral-combat state of the individual; and the individual's mental state of composition make up the spiritual spirit of the armed forces. The intellectual and political aspect is the most significant organizer of the spiritual energy of the armed forces. When it comes to the intellectual and political aspects of personal content, he expresses how mature the issue is. Military personnel will learn about the characteristics of psychological training in this article
Keywords: Military Personnel; Psychological; Training; Aspects